PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP)MELALUI IN HOUSE TRAINING (IHT) DI SDN 04 SUNGAI LIMAU - Nursina Nursina (STKIP Pesisir Selatan, 2019)
Based on observations and supervision conducted by the author, it shows that the pedagogical competence of teachers in developing lesson plans is still low. The purpose of this study is to describe and obtain information about improving the pedagogical competence of teachers in developing Learning Implementation Plans (RPP) through In House Training (IHT) at SDN 04 Sungai Limau. This research is a school action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 6 teachers who taught at SDN 04 Sungai Limau. Research data were collected using observation sheets. Data were analyzed using percentages. The results showed that the implementation of In House Training (IHT) could improve the pedagogical competence of teachers in developing lesson plans. This is evidenced by the initial average score of teacher competence before the program is 74. Then after IHT activities there was an increase in cycle I was 78.70 (good) and after that it increased in cycle II to 87.56 (very good).